DIFFERENCE IN EFFECTIVENESS OF ACUPRESSURE WITH A MIXTURE OF GINGER AND LEMON EXTRACTS ON REDUCING OAT SIDE EFFECTS IN TUBERCULOSIS PATIENTS - Liza Novitasari Wijaya; Tri Hardi Miftahul Ulum; Kiki Rizki Handayani (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Tuberculosis is a disease that attacks the lungs and several other organs caused by Mycobacterium tuberculosis. Tuberculosis remains a global health issue in developing countries, including Indonesia. Anti-tuberculosis drugs are the most important part of pulmonary TB treatment, but these medications often cause side effects. If not controlled, they can cause discomfort and worsen the patient's condition. Acupressure and the administration of ginger and lemon extract serve as non-pharmacotherapy complements to help reduce the side effects of anti-tuberculosis drugs. Methods: This study is quasi-experimental with a two-group pretest-posttest approach involving 30 participants. Acupressure was administered for 7 minutes per day, while a mixture of ginger and lemon extract was given at 8 grams per day. The intervention was provided for four weeks. Body weight was measured using a digital scale, nausea and vomiting were measured using the Rhodes index of nausea, vomiting, and retching, and joint pain was measured using the numeric pain scale. Results: nausea and vomiting with a p-value of 0.00 before and after the treatment. The post-treatment difference test between the two groups did not show significant differences (> 0.05) with a low difference. Conclusions: The administration of acupressure and ginger and lemon extract can help reduce the side effects of tuberculosis treatment